1985
DOI: 10.1136/bmj.290.6475.1103
|View full text |Cite
|
Sign up to set email alerts
|

Trial of relaxation in reducing coronary risk: four year follow up.

Abstract: On screening 192 men and women aged 35-64 were identified as having two or more of the following risk factors: blood pressure > 140/90 mm Hg, plasma cholesterol concentration > 6-3 mmol/l (243 6 mg/100 ml), and current smoking habit ) 10 cigarettes a day. They were randomly allocated to a group for modification of behaviour or to serve as controls. Both groups were given health education leaflets containing advice to stop smoking, to reduce animal fats in the diet, and on the importance of reducing blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
1
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(76 citation statements)
references
References 18 publications
(2 reference statements)
3
71
1
1
Order By: Relevance
“…100 In a follow-up of an earlier British study, 102 Patel and colleagues reported maintenance of lipid profile changes at 8 months postintervention, but no differences between the yoga relaxation/meditation and the control groups at 4 years. 79 Only one RCT, a study of 35 hypertensive Dutch adults (18 intervention group, 17 controls), reported no differences between the intervention and control groups. 101 Of those studies demonstrating positive effects, yoga practice was associated with a 5.8% to 25.2% decrease in total cholesterol, 22.0% to 28.5% reduction in triglycerides, and a 12.8% to 26.0% reduction in LDL, with the observed magnitude of the effects differing by study population and design (Table 5).…”
Section: [105]mentioning
confidence: 99%
See 2 more Smart Citations
“…100 In a follow-up of an earlier British study, 102 Patel and colleagues reported maintenance of lipid profile changes at 8 months postintervention, but no differences between the yoga relaxation/meditation and the control groups at 4 years. 79 Only one RCT, a study of 35 hypertensive Dutch adults (18 intervention group, 17 controls), reported no differences between the intervention and control groups. 101 Of those studies demonstrating positive effects, yoga practice was associated with a 5.8% to 25.2% decrease in total cholesterol, 22.0% to 28.5% reduction in triglycerides, and a 12.8% to 26.0% reduction in LDL, with the observed magnitude of the effects differing by study population and design (Table 5).…”
Section: [105]mentioning
confidence: 99%
“…70 -73 With no appreciable side effects and multiple collateral lifestyle benefits, 70,72,74,75 yoga seems safe, is simple to learn, and can be practiced even by elderly, ill, or disabled individuals. 76 Requiring little in the way of equipment or professional personnel, yoga also seems easy and inexpensive to maintain, with some studies indicating excellent long-term adherence, [77][78][79] even in Western populations. 79 Most importantly, there is a growing body of research suggesting that practice of yoga may reduce IRSrelated risk factors for CVD, and may attenuate signs, reduce complications, and improve the prognosis of those with frank or underlying disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This might mean, for example, training in meditation which has been shown to be effective in encouraging stress control in one's day-to-day life (Patel et al, 1985) in combination with structural changes to allow time and space throughout the working day for individuals to practice this skill. Specific forms such as Mindful Self-Compassion Training (MSC: Neff & Germer, 2013) exist and have a small but growing evidence base in terms of reducing a range of psychological symptoms, including stress (Neff & Germer, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, this is the case for muscle contraction (21) and migraine headaches (22,23), irritable bowel syndrome (24,25), and Raynaud's disease (26). Psychological components in treatment programs have proven effective for hypertension (27), cancer (28,29), and epilepsy (30), to name a few. If exposure to chemicals is a psychological stressor among MCS patients (probably in addition to being a physical trigger of symptoms), a stress-related autonomic reaction also may occur, perhaps superimposed on other physical reactions.…”
Section: Introductionmentioning
confidence: 99%